2001
DOI: 10.1038/nn776
|View full text |Cite
|
Sign up to set email alerts
|

NMDA receptor antagonists sustain LTP and spatial memory: active processes mediate LTP decay

Abstract: Although long-term potentiation (LTP) is long-lasting, it is not permanent and decays within weeks after its induction. Little is known about the processes underlying this decay. Here we assessed the contribution of synaptic activity to LTP decay by determining the effect of the competitive NMDA receptor antagonist CPP on the decay of perforant path-dentate LTP. CPP blocked decay over a one-week period when administered daily following the induction of LTP, and blocked decay of the late, protein-synthesis-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
114
1
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(126 citation statements)
references
References 35 publications
7
114
1
1
Order By: Relevance
“…The competitive NMDAR antagonist CPP was injected intraperitoneally at a dose of 10 mg/kg. Under these conditions, NMDAR activation and LTP induction are blocked for at least 8 hr (Abraham and Mason, 1988;Villarreal et al, 2002). As shown in Figure 3A, BDNF induced a robust potentiation of the fEPSP slope and population spike amplitude in the CPP-treated animals ( p Ͻ 0.05; n ϭ 6).…”
Section: Bdnf-ltp Is Nmda Receptor-independentmentioning
confidence: 82%
“…The competitive NMDAR antagonist CPP was injected intraperitoneally at a dose of 10 mg/kg. Under these conditions, NMDAR activation and LTP induction are blocked for at least 8 hr (Abraham and Mason, 1988;Villarreal et al, 2002). As shown in Figure 3A, BDNF induced a robust potentiation of the fEPSP slope and population spike amplitude in the CPP-treated animals ( p Ͻ 0.05; n ϭ 6).…”
Section: Bdnf-ltp Is Nmda Receptor-independentmentioning
confidence: 82%
“…The (±)CPP dose of 5mg/kg has been shown to disrupt synaptic plasticity processes in the hippocampal formation 12-24 hours following i.p. administration [34].…”
Section: Drugs and Dosage Justificationmentioning
confidence: 99%
“…Two recent studies indicate that LTP persistence over days is in fact subject to ongoing regulation. In one study, LTP (CPP) was injected once daily (Villarreal et al 2001). This treatment also prevented forgetting a learned spatial task.…”
Section: How Long Will Ltp Persist?mentioning
confidence: 99%
“…Although it is potentially misleading to compare the properties of monosynaptic LTP with the properties of memory stored in a network of synapses, none the less the theory has a certain appeal that will seed experimental tests. Indeed, a recent study reported that a treatment that prolonged LTP retention in the dentate gyrus also prolonged memory retention for a hippocampus-dependent spatial memory task (Villarreal et al 2001). Conversely, reduction of LTP maintenance in zif268-knock out mice was associated with reduced retention on several diverse memory tasks (Jones et al 2001).…”
Section: Questions For the Futurementioning
confidence: 99%